2022
DOI: 10.3233/jad-215461
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Substrate of the Motoric Cognitive Risk Syndrome: A Pilot Study Using Amyloid-/Tau-PET and MR Imaging

Abstract: A cross-sectional pilot study to explore the biological substrate of the Motoric Cognitive Risk (MCR) syndrome in a Memory Clinic cohort, using a multimodal imaging approach, was conducted. Twenty participants were recruited and classified as MCR+/−. Amyloid- and tau-PET uptakes, temporal atrophy, white matter hyperintensities, lateral ventricular volume (LVV), and diffusion tensor parameters were compared between groups. No significant differences were found in imaging features related to Alzheimer’s disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 31 publications
0
12
1
Order By: Relevance
“…Therefore, clarifying the relationship between AD pathology and MCR may aid clinical diagnosis and the planning of prevention strategies. To date, only one study has investigated the relationship between MCR and AD pathology using imaging biomarkers (Bommarito et al, 2022) and reported findings inconsistent with the present study. In the above mentioned study, 20 patients with cognitive complaints (8 individuals with MCR and 12 without MCR) were recruited from the Memory Center of the Geneva University Hospitals, and no significant differences in the deposition of amyloid and tau protein in the brain between older adults with MCR and without MCR were found.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Therefore, clarifying the relationship between AD pathology and MCR may aid clinical diagnosis and the planning of prevention strategies. To date, only one study has investigated the relationship between MCR and AD pathology using imaging biomarkers (Bommarito et al, 2022) and reported findings inconsistent with the present study. In the above mentioned study, 20 patients with cognitive complaints (8 individuals with MCR and 12 without MCR) were recruited from the Memory Center of the Geneva University Hospitals, and no significant differences in the deposition of amyloid and tau protein in the brain between older adults with MCR and without MCR were found.…”
Section: Discussioncontrasting
confidence: 99%
“…For cognitively normal individuals, earlier studies have reported significant correlations between slow gait speed and amyloid deposition in the subcortical and cortical areas (Del Campo et al, 2016;Wennberg et al, 2017). However, recent studies did not find increased amyloid deposition in older adults with MCR (Bommarito et al, 2022;Gomez et al, 2022). In this study, for the first time, we compared plasma Aβ42 among older adults with NC, individuals with MCR and those with AD.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations